Somebody I used to know - Mitchell, Wendy (New York : Ballantine Books, 2018)
A memoir by a former British National Heath Service employee and single parent describes her battles with early onset Alzheimer's, the management techniques she has developed to maintain her independence, and her efforts to make sense of her shifting world.
Keywords: Mitchell, Wendy -- Mental health; Mitchell, Wendy -- Mental health; Alzheimer's disease -- Patients -- Great Britain -- Biography; Dementia -- Patients -- Great Britain -- Biography; Alzheimer's disease -- Patients -- Great Britain -- Biography; Dementia -- Patients -- Great Britain -- Biography